Ultrasound in the diagnosis of parotid duct obstruction not caused by sialolithiasis: diagnostic value in reference to direct visualization with sialendoscopy - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Dentomaxillofacial Radiology, 2021)
Objectives: The aim of this study was to evaluate the diagnostic value of ultrasound in the obstructive pathology of the parotic gland not caused by sialolithiasis using sialendoscopy as reference standard.
CRIS-Team WoS Importer:2021-03-26